2016
DOI: 10.5897/cro16.0101
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer awareness, attitude and screening practices in Nigeria: A systematic review

Abstract: Previous research on the breast cancer awareness, attitude and screening practices has produced divergent results. This systematic review aimed to summarise evidence and to compare all existing evidence on the awareness of breast cancer, attitude and screening practices among women in the six geopolitical zones of Nigeria. Overall, 40 articles were included in the final analysis. The search was limited to articles published in English between 2001 and 2014 were included in review. Majority of the respondents i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…These findings are consistent to those of Morse et.al (20) in Tanzania and Marmara et.al (21) in Malta who found variations in both knowledge of symptoms and breast cancer risk factors. The sources of information mentioned in this study included the electronic media (radio and television) and hospitals similar to findings of a review by Ojewusi et.al, (22). These form an important source of information ISSN 2250-3153 http://dx.doi.org/10.29322/IJSRP.9.05.2019.p8953 www.ijsrp.org regarding breast cancer as well as being fertile areas for interventions so as to increase awareness of the cancer.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings are consistent to those of Morse et.al (20) in Tanzania and Marmara et.al (21) in Malta who found variations in both knowledge of symptoms and breast cancer risk factors. The sources of information mentioned in this study included the electronic media (radio and television) and hospitals similar to findings of a review by Ojewusi et.al, (22). These form an important source of information ISSN 2250-3153 http://dx.doi.org/10.29322/IJSRP.9.05.2019.p8953 www.ijsrp.org regarding breast cancer as well as being fertile areas for interventions so as to increase awareness of the cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Those who were knowledgeable on the procedure were 2.6 times more likely to have been screened. A systematic review by Ojewusi et.al, (22) found that lack of knowledge on how to carry out a SBE was expressed by as one the most important factors in its uptake. Similarly in Lebanon, women who were more confident on their ability to perform a SBE were 2.65 times more likely to practice it.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies report approximately 80% to 92% of Nigerian women are aware of mammography screening, only 3% to 10% are reported to have actually undergone the screening. 41 Studies have revealed that Nigerian women with a higher level of education exhibit more knowledge about breast self-examination (BSE), tend to believe that early BC detection leads to better survival rates, and are more likely to practice BSE compared with those with a lower level of education. 42 - 44 Studies have also revealed that most Nigerian health care providers lack sufficient knowledge of BC risk factors and the procedure for BSE .…”
Section: Nature Versus Nurture: What We Know and Need To Know About Nmentioning
confidence: 99%
“…The breast cancer burden differs between countries and regions showing variations in incidence, mortality and survival rates [9][10]. Breast cancer-related deaths in Nigeria reached 13,264 or 0.70% of total deaths and showed that Nigeria ranks 4 th in the world [11].…”
Section: Introductionmentioning
confidence: 99%
“…WHO [23] found out that breast cancer deaths in Nigeria reached 13,264 or 0.70% of total deaths and showed that Nigeria ranks 4 th in the world [11].…”
Section: Introductionmentioning
confidence: 99%